2005
DOI: 10.1051/kmae:2005032
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship Between Female Size and Egg Size in the Freshwater Crayfish Austropotamobius Torrentium

Abstract: The aim of our research was to gather information about the reproduction cycle of Austopotamobius torrentium in Croatia. The research was conducted between October 1998 and April 2000 in streams on the Medvednica Mountain (north-west Croatia). We caught 767 females, of which 92 (11.99%) were berried. Berried females were captured from the beginning of November until mid June of the following year. Total length (from the tip of the rostrum to the end of telson) of the smallest female with pleopodal eggs was 5.4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
12
1
1

Year Published

2006
2006
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 13 publications
2
12
1
1
Order By: Relevance
“…Moreover, females showed positive allometric abdomen width growth, whereas such a growth in males was isometric. This finding corresponds with the often demonstrated fact that a larger abdomen increases the capacity for carrying eggs, improves egg attachment and as a result increases the whole reproductive success (Grandjean et al, 1997;Maguire et al, 2002;Reynolds, 2002;Maguire et al, 2005). Although Thomas and Ingle (1971) and Lowery (1988) mentioned the positive allometry in the abdomen width only in females after reaching sexual maturity, we found, similarly to Grandjean et al (1997), that significant sexual dimorphism in abdomen width already exists before the pubertal moult.…”
Section: Figuresupporting
confidence: 87%
See 1 more Smart Citation
“…Moreover, females showed positive allometric abdomen width growth, whereas such a growth in males was isometric. This finding corresponds with the often demonstrated fact that a larger abdomen increases the capacity for carrying eggs, improves egg attachment and as a result increases the whole reproductive success (Grandjean et al, 1997;Maguire et al, 2002;Reynolds, 2002;Maguire et al, 2005). Although Thomas and Ingle (1971) and Lowery (1988) mentioned the positive allometry in the abdomen width only in females after reaching sexual maturity, we found, similarly to Grandjean et al (1997), that significant sexual dimorphism in abdomen width already exists before the pubertal moult.…”
Section: Figuresupporting
confidence: 87%
“…However, most of the above mentioned studies are focused on A. pallipes and only few biometric analyses concerning A. torrentium have been performed up to now (e.g. Streissl and Hödl, 2002;Maguire et al, 2005;Sint et al, 2005;Maguire and Klobučar, 2009;Pârvulescu, 2010). Consequently, the aim of this study is to supply missing data about the morphology of the stone crayfish, including on the sexual dimorphism, and the evaluation of allometric growth of selected size parameters.…”
Section: Introductionmentioning
confidence: 99%
“…STUCKI (2002) presented the following average pleopodal fecundities per female: noble crayfish 150, stone crayfish 60, narrow-clawed crayfish 180 and signal crayfish 114 eggs per one female. MAGUIRE et al (2005) founded a mean pleopodal fecundity of 62 eggs, ranging between 30 and 104 eggs, for the stone crayfish. The big eggs losses happen during the winter incubation among these crayfish species (CELADA et al, 2005a,b), which is a significant advantage for the spiny-cheek crayfish, which carries eggs for one to two months only in spring (as described already by ANDREWS, 1907).…”
Section: Discussionmentioning
confidence: 99%
“…This suggests that the discrepancy between the two measures of fecundity is chiefly due to poor egg attachment, rather than to factors such as egg resorption or incomplete fertilisation (SAVOLAINEN et al, 1996;REYNOLDS, 2002). Both ovarian and pleopodal fecundity correlated with female size (STYPIŃSKA, 1973;SAVOLAINEN et al, 1996;AUSTIN, 1998a;SCHULZ and ŚMIETANA, 2001;HARLIOĞLU et al, 2004;MAZLUM and EVERSOLE, 2004;NAKATA and GOSHIMA, 2004;HUBER and SCHUBART, 2005;MAGUIRE et al, 2005), but the relationship between the egg number and body size was strongly influenced by environmental conditions (REYNOLDS, 2002). Different authors evaluated the pleopodal fecundity just after ovulation (ABRAHAMSSON, 1971;AUSTIN, 1998a,b;LEONARD et al, 2001;NAKATA and GOSHIMA, 2004;CELADA et al, 2005a;SÁEZ-ROYUELA, 2005), during incubation (JONES, 1995;LEWIS and HORTON, 1997;MAZLUM and EVERSOLE, 2004;CELADA et al, 2005a,b;SÁEZ-ROYUELA, 2005) or just before hatching (SÖDERBÄCK, 1995;SAVOLAINEN et al, 1996;CELADA et al, 2005b;SÁEZ-ROYUELA et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Significant relation was also found between egg size and mother size, differently by the study of Sàez-Royuela et al (2006), but not between egg size and embryonic stages. However, Woodlock and Reynolds (1988a) showed that larger females have bigger eggs and that is also the case in A. torrentium (Maguire et al 2004).…”
Section: Discussionmentioning
confidence: 92%